SOME FEATURES OF LEGAL REGULATION OF ARTIFICIAL INTELLIGENCE: FOREIGN AND NATIONAL EXPERIENCE - Г.Г. Галиакбарова (Хабаршы. Заң сериясы)
This paper is research devoted to the study of approaches to the legal regulation of the field of artificial intelligence both in Kazakhstan and in some foreign countries that succeed in this matter. The paper also provides a structured understanding of the prospects for the governance of artificial intelligence in Kazakhstan, as well as recommendations for the use of modern international standards and practices. Special attention is paid to the experience of the United States, the European Union, China, and Russia. Based on the results of critical analysis of foreign experience, several measures have been proposed, including the definition of the concept of artificial intelligence and the status of “new” subjects of law at the legislative level. At the same time, the paper notes that the artificial intelligence legal provisions at the level of a codified act does not require haste and needs detailed elaboration. This approach will ensure clarity and efficiency of regulation, as well as the necessary flexibility for such a rapidly developing area of social relations. The aim of this study is to determine the place of artificial intelligence, and possible areas of its application, and to consider the main problems. Methods: analysis and synthesis, deduction and induction, comparative legal. The conducted research is of potential value for domestic legislators, lawyers, human rights activists, students, and anyone interested in the legal regulation of artificial intelligence.